Improving stakeholder engagement in climate change risk assessments: insights from six co-production initiatives in Europe - André, Karin; Gerger Swartling, Åsa; Englund, Mathilda; Petutschnig, Linda; Attoh, Emmanuel M. N. A. N.; Milde, Katharina; Lückerath, Daniel; Cauchy, Adeline; Botnen Holm, Tara; Hanssen Korsbrekke, Mari; Bour, Muriel; Rome, Erich (Frontiers in Climate, 2023)
It is increasingly recognized that effective climate risk assessments benefit from well-crafted processes of knowledge co-production involving key stakeholders and scientists. To support the co-production of actionable knowledge on climate change, a careful design and planning process is often called for to ensure that relevant perspectives are integrated and to promote shared understandings and joint ownership of the research process. In this paper, we aim to further refine methods for co-producing climate services to support risk-informed decision-support and adaptation action. By drawing on insights and lessons learned from participatory processes in six case studies in Northern and Central Europe, we seek to better understand how associated challenges and opportunities arising in co-production processes play out in different case-specific contexts. All cases have applied a standardised framework for climate vulnerability and risk assessment, the impact chain method. The analysis builds on multiple methods including a survey among case study researchers and stakeholders, interviews with researchers, as well as a project workshop to develop collective insights and synthesis of results. The results illustrate case studies’ different approaches to stakeholder involvement as well as the outputs, outcomes, and impacts resulting from the risk assessments. Examples include early indications of mutual learning and improved understanding of climate risks, impacts and vulnerability, and local and regional decision contexts, as well as actual uptake in planning and decision contexts. Other positive outcomes concern scientific progress and contribution to methodological innovations. Overall, our study offers insights into the value of adopting good practices in knowledge co-production in impact chain-based climate risk assessments, with wider lessons for the climate services domain. While collaborations and interactions have contributed to a number of benefits some practical challenges remain for achieving effective co-production processes in the context of climate change and adaptation. To overcome these challenges, we propose a carefully designed but flexible and iterative participatory approach that enables joint learning; reassessment of stakeholder needs and capacities; and co-produced, actionable climate services with the potential to catalyse climate action.